Comparison of coordinative abilities of child wrestlers and judokas - Çoruh, Y.; Zengin, S. (Journal of Education and Training Studies, 2019)
The aim of this research is to compare the coordinative abilities of child wrestlers and judokas. Totally 52 athletes were included into the research by taking consent from their families; 26 judoka children whose age average is 13.45±0.506 years, height average is 1.52±0.090 mt and body weight average is 47.52±13.193 kg and 26 judoka whose age average is 14.75±0.639 years, height average is 1.59±0.064 mt and body weight average is 49.85±8.786 kg. All risks and benefits pertaining to the research were explained to the parents of athletes and they were asked to sign the university confirmed voluntary permission form. Numbered medicine ball running test, Backward Medicine Ball Throw Test and sprint test to the given rhythm were used for the purpose for determining the orientation, differentiation and rhythm performances in regard to coordinative abilities of the individuals participating into the research. SPSS 22 program was used for the analysis of the data obtained. It was found out according to the result of One Sample Kolmogorov-Smirnov test performed that data related with rhythm times exhibited normal distribution, data related with orientation times and differentiation scores did not exhibit normal distribution. For this reason, while Independent Samples T test was used in comparison of data related with rhythm times by the type of sports, Mann Whitney U test was used in comparison of data related with orientation times and differentiation scores by the type of sports. Once the results related with research were examined, while it was seen that the rhythm times and orientation times of wrestlers were significantly better than those of judoka, it was concluded that any significant difference was not available for the differentiation ability.